Teacher Efficacy, Collective Self-Esteem, and Organizational Commitment of Childcare Teachers: A Moderated Mediation Model of Social Support - Chung, Myung-Sun (Frontiers in Psychology, 2019)
This study explored the moderated mediation model from the viewpoint of whether the job resource of social support can reinforce relationships among teacher efficacy, collective self-esteem, and organizational commitment based on the Job Demands-Resources (JD-R) model. A sample of 212 childcare teachers completed a self-report battery that included measures of teacher efficacy, collective self-esteem, organizational commitment, and social support. The results indicated that collective self-esteem partially mediated the relationship between teacher efficacy and organizational commitment. The findings also demonstrated that teacher efficacy translated into a higher organizational commitment among teachers that perceive relatively higher degrees of social support in both the indirect effect through collective self-esteem and the direct effect without collective self-esteem. The study highlights the need to establish public childcare policies that are conducive to increasing social support for teachers. Based on these results, the benefits of understanding this moderated mediation path, the limitations of the study, and future research directions are discussed.